Chronic non-cancer pain among adults with substance use disorders: Prevalence, characteristics, and association with opioid overdose and healthcare utilization. (1st April 2020) - John, William S.; Wu, Li-Tzy
Highlights: Most patients with substance use disorders (SUDs) had chronic pain (CP) conditions. The prevalence of CP was greater among females than males for most SUDs. CP was associated with significant multicomorbidity among patients with SUDs. Results suggest CP may be relatively untreated in patients with non-opioid SUDs. CP may play a greater role in opioid overdoses among females than males with SUDs. Abstract: Background: Chronic non-cancer pain (CNCP) among patients with substance use disorder (SUD) poses a risk for worse treatment outcomes. Understanding the association of CNCP with SUD is important for informing the need and potential benefits of pain assessment/management among those with SUDs. Methods: We analyzed electronic health record data from 2013 to 2018 among adults aged ≥18 years ( N = 951, 533; mean age: 48.4 years; 57.4 % female) in a large academic healthcare system. Adjusted logistic regression models were conducted to estimate the association of CNCP conditions with opioid overdose, emergency department utilization, and inpatient hospitalization stratified by different SUD diagnoses and by gender. Results: Among the total sample, the prevalence of CNCP was 46.6 % and any SUD was 11.2 %. The majority of patients with a SUD had CNCP (opioid: 74.7 %; sedative: 72.3 %; cannabis: 64.3 %; alcohol: 58.7 %; tobacco: 59.5 %). The prevalence of CNCP was greater in females vs. males for most SUD diagnoses. The presence of CNCP was associated with more mental health disorders and chronic medical conditions among each SUD group. CNCP was associated with significantly decreased odds of overdose among those with opioid use disorder but increased odds of overdose and healthcare utilization among other SUDs. CNCP was positively associated with overdose in females, but not males, with alcohol or non-opioid drug use disorders. Conclusions: The direction and magnitude of the association between CNCP and negative health indicators differed as a function of SUD type and gender, respectively. Greater awareness of potential unmet pain treatment need may have implications for improving SUD outcomes.